Surviving Desire & Co. - Hartley, Hal; Spiller, Michael; Donovan, Martin; Feaster, George; Gosse, Bob; Dunnock, Patricia
Six films shot on 16mm in the 80s and early 90s. All restored in 2019 from the original negatives. They have never looked better. From 1991, "Surviving Desire", starring Martin Donovan and Mary Ward, "Theory of Achievement", starring Elina Löwensohn and Bill Sage, and "Ambition", starring George Feaster. "Opera No. 1" (1994), starring Parker Posey, Adrienne Shelly, James Urbaniak and Patricia Dunnock. And two films from the 80s, "Kid" (1984), and "The Cartographer's Girlfriend" (1987). [www.halhartley.com]